El hábeas corpus como garantía de protección del derecho a la vida en el contexto de la pandemia Covid 19. - Ramos Ramos, Miguel Asdrúbal (2021)
The current research project entitled: "Habeas corpus as a guarantee of protection of the right to life in the context of the COVID 19 pandemic" focuses its origin in the research line of Constitutional Rights and Guarantees, orienting its study to the right to life and how this can be protected through the jurisdictional guarantee of habeas corpus, in the context of the COVID 19 pandemic. The Constitution of the Republic of Ecuador and the Organic Law of Jurisdictional Guarantees and Constitutional Control is clear in stating that the jurisdictional guarantee of habeas corpus has, among its objectives, the protection of the right to life of persons deprived of liberty, constituting a prerequisite for the exercise of other rights, guaranteeing not only the right not to be deprived of it, but acquires broader and more significant scope, involving the right to access all those conditions that ensure a dignified life. The high rates of contagion and deaths caused by the COVID 19 pandemic have been factors that have motivated the prison population to protect their lives using the jurisdictional guarantee of habeas corpus, arguing that these centers of deprivation of liberty are not adequate places through which the consequences of the pandemic could be prevented or treated, this is due to how people live in these detention centers, such as overcrowding, overcrowded conditions, inadequate infrastructure, insufficient medical supplies, and lack of specialized medical personnel, determining factors that put their lives in imminent danger. The main purpose of this research work is to describe how the jurisdictional guarantee of habeas corpus is conceived and applied in our legislation through a critical, legal, jurisprudential, and doctrinal study of habeas corpus cases, filed in the context of the COVID 19 pandemic, as a mechanism for the protection of the right to life of persons deprived of their liberty.